Dynamic characterization of dual stage micro actuator - Chua, Siong Pau (2014)
The importance of storage capacity in a hard disk drive (HDD) grows over the years. One way to increase the capacity is to improve the tracking performance of the read/write head. In order to achieve that, micro thermal actuator is introduced which has more accuracy for driving the head to read or write on the right track. In thermal actuation, the resonant frequency and sensitivity achieved can be much higher than the other actuation technology. In addition, the strain caused by the heat can produced a higher lateral motion at a small amount of voltage.